The Effect of Influencer Marketing, Social Media Engagement, and Product Knowledge on Brand Awareness in Tiktok Shop - Sujoko Sujoko; Febriyani Febriyani; Agung Hartadi (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to determine the effect of influencer marketing, social media engagement, and product knowledge on brand awareness in TikTok Shop. This study uses primary data with a data collection method through distributing questionnaires that have been tested for validity and reliability. The sample consists of 96 respondents, selected with purposive sampling. This study employs a quantitative descriptive method. The data analysis conducted in this study was a classical assumption test, multiple linear regression analysis and hypothesis testing with the Statistical Program for Social Science (SPSS) tool. The results of the data analysis showed that influencer marketing, social media engagement, and product knowledge together had an effect on brand awareness. Partially, influencer marketing and product knowledge have a significant positive effect on brand awareness, which means that the more effective the influencer marketing provided by business actors, the higher the product knowledge received by consumers, so that it can increase brand awareness. However, social media engagement has no effect on brand awareness. And the coefficient of determination or r-square with a value of 0.473 means that the variables influencer marketing, social media engagement, and product knowledge have an effect on the brand awareness variable on Tiktok Shop by 47.3% while the remaining 52.7% is influenced by other factors not observed in this study.